(untitled) (Biological Sciences - PJSIR, 1994)
Steam activated carbon of high surface area does not show any Palladium ions adsorption. Treatment of this carbon with HF acid increases to a great extent the gas adsorption capacity expressed as nitrogen surface area as well as the adsorption capacity of Palladium ions from aqueous solution. HHB was loaded in different amounts on to these carbons. The acid sites represent the active fraction of the surface on which the adsorption of Palladium ions proceed. The uptake of Palladium ions by HHB treated carbons is related to the total number ofHHB molecules loaded on the carbon surface.